Types of bullies at workplace in Malaysia - Khalidass, Thivya; Chethiyar, Saralah Devi Mariamdaran; Equatora, Muhammad Ali (Journal of Advanced Guidance and Counseling, 2023)
Purpose - The purpose of this study was to examine the type of bully’s perception of workplace in Malaysia. This study can reveal the type of bullies that happens at work because most employees are not aware or know that they are being bullied at work.Method - The population of this study is employees of Sungai Petani Social Security Organization. This selection of samples in this study using purposive sampling method and selected 45 persons. Research data was obtained through the distribution of a set of questionnaires. The instrument used in this study is the Revised Malaysian Bullying Questionnaire (R-MBQ).Result - The results showed that that the perception of bullying among employees of the Sungai Petani Society is at a low level.Implication - This method suggests prevailing bullying behavior in public or private sector at Malaysia through the types of bullying behavior such as bullying in the form of personal attacks, bullying by looking down, work-related bullying and bullying by physical violence.Originality - This research is the first study that used intervening variable regarding types of bullying among employees.***Tujuan - Tujuan dari penelitian ini adalah untuk mengetahui jenis persepsi pengganggu di tempat kerja di Malaysia. Penelitian ini dapat mengungkap jenis bully yang terjadi di tempat kerja karena sebagian besar karyawan tidak menyadari atau mengetahui bahwa mereka sedang diintimidasi di tempat kerja.Metode - Populasi dari penelitian ini adalah karyawan Organisasi Jaminan Sosial Sungai Petani. Pemilihan sampel dalam penelitian ini menggunakan metode purposive sampling dan terpilih sebanyak 45 orang. Data penelitian diperoleh melalui penyebaran seperangkat kuesioner. Instrumen yang digunakan dalam penelitian ini adalah Revised Malaysian Bullying Questionnaire (R-MBQ).Hasil - Hasil penelitian menunjukkan bahwa persepsi perundungan di kalangan karyawan Masyarakat Sungai Petani berada pada tingkat rendah.Implikasi - Metode ini menunjukkan perilaku bullying yang berlaku di sektor publik atau swasta di Malaysia melalui jenis-jenis perilaku bullying seperti bullying dalam bentuk serangan pribadi, bullying dengan meremehkan, bullying yang berhubungan dengan pekerjaan, dan bullying dengan kekerasan fisik.Orisinalitas - Penelitian ini merupakan penelitian pertama yang menggunakan variabel intervening mengenai jenis-jenis perundungan di kalangan karyawan.